2016
DOI: 10.1501/tarimbil_0000001377
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, agronomical, phenological and stand persistence traits of some wild narrowleaf birdsfoot trefoil (lotus tenuis waldst. & kit.) populations

Abstract: Existing information on the ecology, distribution and plant traits of Lotus taxa is scant for the natural flora of Turkey, which is one of the most important countries in the Mediterranean zone for genetic resources and genetic diversity of these species. Therefore, the aim of this study was to determine (i) morphologic, agronomic, phenologic, stand persistence traits and growth habits of some wild narrowleaf birdsfoot trefoil (NBT; Lotus tenuis Waldst. & Kit.), and (ii) the relationships between these traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In the first part of the present study, the morphologic, agronomic and phonologic traits of 86 NBT populations and the relationships between these traits and geographical features of the natural habitats were determined (Uzun et al, 2016). The results from this study indicated that NBT populations were present in all ranges of altitude, although there was a decrease in present frequency of NBT with increasing altitude.…”
Section: Resultsmentioning
confidence: 78%
“…In the first part of the present study, the morphologic, agronomic and phonologic traits of 86 NBT populations and the relationships between these traits and geographical features of the natural habitats were determined (Uzun et al, 2016). The results from this study indicated that NBT populations were present in all ranges of altitude, although there was a decrease in present frequency of NBT with increasing altitude.…”
Section: Resultsmentioning
confidence: 78%